Perimolysis: case report - Daniel, Carolina Pratti; Ricci, Hérica Adad; Boeck, Eloísa Marcantonio; Bevilacqua, Flavia Magnani; Cerqueira-leite, Jaqueline Braga Barbosa (Faculdade São Leopoldo Mandic, 2015)
Perimolysis is a form of dental erosion, characterized by dental tissue demineralization without bacterial involvement. It can be of intrinsic or extrinsic origin. Extrinsic origin is considered when it is caused by excessive consumption of acid drinks and foods such as soft drinks, alcoholic beverages, acid fruit and prescription drugs for daily use. When caused by gastrointestinal disorders, such as those resulting from bulimia, anorexia nervosa and gastroesophageal reflux, it is considered of intrinsic origin. The acid action can cause erosion on palatal/lingual incisor surfaces, and occlusal and palatal/lingual posterior tooth surfaces causing pain (dental hyperesthesia). Treatment is often multidisciplinary, and the causes should be identified, eliminated or controlled. In dentistry, the approach must include preventive measures to reduce future risks, and restorative intervention using materials such as glass ionomer cement, resin composite, or endodontic and prosthetic rehabilitation in more complex cases. The aim of this study was to describe the restorative treatment in the case of a patient with this condition.

Perimólise é uma forma de erosão dentária, caracterizada pela desmineralização do tecido dental sem envolvimento bacteriano, de origem intrínseca ou extrínseca. É considerada de origem extrínseca quando causada pelo consumo excessivo de bebidas, alimentos e substâncias ácidas, como refrigerantes, bebidas alcoólicas, frutas ácidas e medicamentos de uso contínuo. Denomina-se intrínseca quando causada por distúrbios gastrintestinais como os que ocorrem como conseqüência da bulimia, da anorexia nervosa e do refluxo gastresofágico. A ação ácida pode causar erosão nas faces palatina/lingual dos incisivos e palatina/lingual e oclusal dos dentes posteriores levando a dor, ou seja, hiperestesia dental. O tratamento geralmente é multidisciplinar, devendo identificar e eliminar ou controlar as causas. A abordagem odontológica deve associar medidas preventivas para diminuir riscos futuros e intervenção restauradora utilizando materiais como cimento ionômero de vidro, resina composta ou até mesmo endodontia e reabilitação protética para casos mais complexos. Este trabalho teve como objetivo descrever o tratamento restaurador de um caso clínico de paciente com esta patologia.
Perimólise: relato de caso clínico
Keywords: Acidity; Dental enamel; Esthetics; Tooth erosion; Acidez; Esmalte dentário; Estética; Erosão dentária